2017
DOI: 10.1159/000477566
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Adrenaline Use in Anaphylaxis: A Multicentre Register

Abstract: Background: The use of intramuscular adrenaline to treat anaphylaxis is suboptimal, despite being the first-line treatment recommended by national and international anaphylaxis guidelines. Fear of potentially severe side effects may be one of the underlying factors. The aim of this study was to assess the incidence and severity of adverse side effects after the use of adrenaline in anaphylaxis, as well as potential risk factors. Methods: Observational study based on a multicenter online registry of cases of ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(18 citation statements)
references
References 25 publications
0
13
0
2
Order By: Relevance
“…Several studies from USA, UK, and Australia suggested that the incidence of anaphylaxis is on a gradual rise over the last two decades [714]. To estimate the incidence, prevalence, and triggers, scientists have used different methodologies including patients’ case reports [1517], international medical coding systems [79, 1824], hospital admission rates [11, 13, 25, 26], public surveys and epinephrine dispense records [10, 12, 21, 25, 27, 28]. These studies have demonstrated that distribution of anaphylaxis tends to fluctuate based on age, gender, race, geographical residence, and socioeconomic status of involved subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies from USA, UK, and Australia suggested that the incidence of anaphylaxis is on a gradual rise over the last two decades [714]. To estimate the incidence, prevalence, and triggers, scientists have used different methodologies including patients’ case reports [1517], international medical coding systems [79, 1824], hospital admission rates [11, 13, 25, 26], public surveys and epinephrine dispense records [10, 12, 21, 25, 27, 28]. These studies have demonstrated that distribution of anaphylaxis tends to fluctuate based on age, gender, race, geographical residence, and socioeconomic status of involved subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Complications of epinephrine overdoses have been reported a number of times in the published literature and can include arrhythmia, hypertension, chest pain, tremor, anxiety, paleness, headache, peripheral vasoconstriction and nausea/vomiting. [67] Reported severe complications associated with iatrogenic epinephrine overdosages have included ventricular dysfunction, myocardial infarction, cardiac arrest, pulmonary edema and renal failure. [891011] Adverse events tend to be more severe in older patients that receive high doses of epinephrine via the intravenous routes.…”
Section: Discussionmentioning
confidence: 99%
“…[891011] Adverse events tend to be more severe in older patients that receive high doses of epinephrine via the intravenous routes. [712] Laboratory findings of excessive epinephrine dosing may include hyperglycemia, leukocytosis and hypokalemia. Treatment of epinephrine overdose is generally supportive in nature and targeted at specific symptom management.…”
Section: Discussionmentioning
confidence: 99%
“…Pero advertimos que en nuestros resultados el 18% eligió la vía intravenosa y 35% dosis superiores a las recomendadas. Cardona et al (34) describieron que la administración de la adrenalina intravenosa y la utilización de dosis mayores a las recomendadas se asociaron a mayor frecuencia de efectos adversos pero no observaron mayor morbimortalidad.…”
Section: Anafilaxia En Pediatría -Fustiñana Al Et Alunclassified